Coverage of Soft Tissue Dehiscences Around Osseointegrated Implants in Aesthetic Areas - Surgical-Prosthetic Approach and Patient Satisfaction - Bayarri Bernet, Laura (Archive of Orofacial Data Science, 2024)
AIM: The aim of the study is to assess the success rate of the available methods for the treatment of soft tissue dehiscences in osseointegrated implants in the anterior area. The success rate will be determined based on the degree of coverage both short and long-term as well as clinical and aesthetic parameters. METHODS: Clinical trials and case reports on the treatment of soft tissue dehiscences between 0.7 mm ± 0.3 mm and 3.0 mm ± 0.8 mm in anterior osseointegrated implants were analyzed. The data collection was carried out in PubMed and 17 articles were included. RESULTS: A total of 144 osseointegrated implants in the anterior area with soft tissue dehiscences were evaluated in this bibliographic review. The possibilities of coverage in millimeters range from 0.17 mm to 3 mm. Coronally advanced flap was associated with soft tissue coverage. The use of subepithelial connective tissue graft (SCTG) results in soft tissue dehiscence reduction. Crown removal one month before surgery and chamfers or shoulders in the abutment reduction provides better healing of the soft tissue after surgery. Some authors also achieved soft tissue coverage with the use of acellular dermal matrix (ADM), but the results are still controversial. CONCLUSION: The use of SCTG to cover STD in osseointegrated implants is a reliable method, although complete coverage is not achieved in all cases. The use of ADM seems to be a shorter and less painful alternative treatment, but the results are not yet predictable.